EFFICIENCY OF PHET AND CROCODILE PHYSICS SIMULATORS IN DISTANCE LEARNING PHYSICS FOR ENGINEERING SPECIALTIES - Мартинова, Олена (SWorldJournal, 2025)
The study investigates the impact of integrating PhET and Crocodile Physics simulations into an online “General Physics” course for engineering undergraduates at Zhytomyr Polytechnic State University during the 2024/2025 academic semester. Two pre-formed